A pure spinor twistor description of the D = 10 superparticle - Sepúlveda, Diego García [UNESP]; Guillen, Max (Springer Nature, 2020)
We present a novel twistor formulation of the ten-dimensional massless super-particle. This formulation is based on the introduction of pure spinor variables through a field redefinition of another model for the superparticle, and in the new description we find that the super-Pauli-Lubanski three-form naturally arises as a constraint. Quantization is studied in detail for both models and they are shown to correctly describe the D = 10 super-Yang-Mills states.
Keywords: BRST Quantization; Supersymmetric Gauge Theory